Eksplorasi Paku-Pakuan (Pteridophyta) Di Kawasan Cagar Alam Mandor Kabupaten Landak - Irwan Lovadi, Utin Purnawati, Masnur Turnip, (Jurnal Protobiont, 2014)
Ferns (Pteridophyta) have an important role in forest ecosystems, but the destruction of the forest decreased the amount of ferns. The existences of ferns in the forest are in danger due to gold mining, logging and forest fires. This study was conducted to investigate ferns diversity in Mandor Nature Reserve in Landak Regency. The study was done for 4 months from July to November 2012. Cruise Method was used to explore ferns within the nature reserve. The study found that there were 21 species consisting of 1 class and 14 families. Polypodiaceae family is the most commonly found, while Aspleniaceae, Blechnaceae, Davalliaceae, Dennstaedtiaceae, Dryopteridaceae, Gleicheniacea, Lindsaeaceae, Lycopodiaceae, Lygodiaceae, Nephrolepidaceae, Pteridaceae, Selaginellaceae and Woodsiaceae were not common in the nature reserve.